2021
DOI: 10.1186/s12870-021-03046-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study and its applications in the non-model crop Sesamum indicum

Abstract: Background Sesame is a rare example of non-model and minor crop for which numerous genetic loci and candidate genes underlying features of interest have been disclosed at relatively high resolution. These progresses have been achieved thanks to the applications of the genome-wide association study (GWAS) approach. GWAS has benefited from the availability of high-quality genomes, re-sequencing data from thousands of genotypes, extensive transcriptome sequencing, development of haplotype map and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 147 publications
0
23
0
Order By: Relevance
“…Likewise, a small number of associated loci for TSW were found in bi-parental sesame populations [ 3 , 60 ], which may suggest that this trait is under less complex genetic control or under the regulation of many small-effect genomic regions. The absence of significant genomic signals for TSW (as well as other traits in the current study) indicates that other approaches, such as a multi-locus GWAS model [ 61 ] or genomic prediction [ 62 ], may contribute to the understanding of the genetic basis. The positive phenotypic and genomic correlations between TSW and SYPP (0.37 and 0.44, respectively), and between SNPP and SYPP (0.86 and 0.93) on one side, and the absence of both correlations between TSW and SNPP (− 0.04 and 0.17, respectively) on the other side, open up the possibility to breed simultaneously for both traits and improve yield.…”
Section: Discussionmentioning
confidence: 92%
“…Likewise, a small number of associated loci for TSW were found in bi-parental sesame populations [ 3 , 60 ], which may suggest that this trait is under less complex genetic control or under the regulation of many small-effect genomic regions. The absence of significant genomic signals for TSW (as well as other traits in the current study) indicates that other approaches, such as a multi-locus GWAS model [ 61 ] or genomic prediction [ 62 ], may contribute to the understanding of the genetic basis. The positive phenotypic and genomic correlations between TSW and SYPP (0.37 and 0.44, respectively), and between SNPP and SYPP (0.86 and 0.93) on one side, and the absence of both correlations between TSW and SNPP (− 0.04 and 0.17, respectively) on the other side, open up the possibility to breed simultaneously for both traits and improve yield.…”
Section: Discussionmentioning
confidence: 92%
“…The GWAS is powerful for identifying candidate genes corresponding to natural variation of traits in field crops as well as in horticultural plants ( Su et al, 2019 ; Alseekh et al, 2021 ; Berhe et al, 2021 ). A larger population size has been used for association analysis in field crops, such as rice ( Huang et al, 2012 ), soybean ( Zhou et al, 2015 ), and maize ( Maldonado et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Liang et al (2021) reported that four genomic regions were associated with five significant QTLs (qRSL1.2, qRSL1, qRSL7and qRSL12/qRSL12) based on the respective flanking markers in each drought-resistant gene QTL. Although 465 genes were identified in these four genomic regions, only 347 genes were functionally annotated; the remaining 118 genes were unknown Although more than 300 QTLs and more than 250 candidates have been identified in sesame, QTLs and important genes for chlorophyll yield, heat tolerance, waterlogging tolerance, and other traits are under investigation (Berhe et al, 2021). Different genotypes respond differently to waterlogging stress and the resistant genotypes remain more stable during waterlogging, whereas more sesame genotypes showed sensitivity to waterlogging stress (Wang et al, 2016a).…”
Section: Genes and Qtls Associated With Abiotic Stress Tolerance In S...mentioning
confidence: 99%